Evaluation of the impact of hydrogen-rich water on the quality attribute notes of butter. Issue 4 (21st November 2022) - Ceylan, M. Murat; Bulut, Menekşe; Alwazeer, Duried; Koyuncu, Mubin
Abstract: The effects of washing raw butter with hydrogen-rich water (HRW), prepared with hydrogen (H2 ) and/or magnesium (Mg), on butter quality were investigated in this research paper. During the washing process, titratable acidity (TA) decreased by 12% for all washed samples. During the storage period, TA increased by 28% and 93% (control), 14% and 58% (H2 ), and 10% and 66% (Mg) for the 60 th and 90 th days, respectively. Peroxide value (mEq O2 /kg) increased to 2.76 and 8.83 (control), 1.92 and 7.25 (H2 ), and 2.02 and 8.12 (Mg) for the 60 th and 90 th days. HRW samples showed the lowest acid degree value (ADV) and the highest color notes (L*, C*, and h). The HRW treatment of raw butter has shown improving effects on the product without any harmful residuals in the final product or the environment.